Thyroglossal cyst with oropharyngeal propagation in 40 year-old patient - Miroslav Obrenović; Siniša Kojić; Vekoslav Mitrović; Mirjana Ćuk; Borko Davidović; Siniša Šolaja (Биомедицинска истраживања, 2018)
Introduction: Thyroglossal cyst represents the most common congenital anomaly of the neck and it occurs in approximately 7% of the overall population. It develops as a consequence of obliteration failure of ductus thyreoglossus during migration of thyroid gland in embryogenesis. It is usually diagnosed during the first decade of life by clinical examination, echosonography, multislice computed tomography (MSCT) and/or magnetic resonance imagining (MRI) of the brain and neck, fine needle aspiration (FNA) and cytological analysis of the FNA content. Treatment is surgical using the Sistrunk procedure. Case report. The 40 year-old patient was hospitalized for the diagnostics and treatment of the tumor of submental and submandibular region as well as of oral cavity, with right-sided dislocation of the tongue followed by difficulties in swallowing and speech. In his early childhood, the patient detected a subcutaneous formation under the chin that expanded gradually. Clinical examination revealed the subcutaneous tumor mass that affected submental and both submandibular regions, predominantly left-sided with the intraoral presentation of submucosal tumor that completely filled oropharynx and dislocated the tongue to the right side. MSCT of the mouth and neck floor indicated an irregularly oval tumor of 120 x 95 x 90 mm, with its upper pole reaching the hard palate. The tumor filled the oral cavity and descended anterolaterally and more to the left side into the neck region to the hyoid bone, dislocating the tongue, eosophagus as well as pharyngeal and laryngeal structures to the right side. Cytological analysis of the FNA content confirmed the presence of thyroglossal cyst. Under nasotracheal intubation, the operation using the Sistrunk procedure was performed, with the removal of cystic tumor, and medial portion of hyoid bone, as well as with the tongue reposition. There were no complications during post-operative period. Speech and swallowing functions were completely rehabilitated. The results of pathohistological analysis confirmed the presence of thyroglossal cyst. Conclusion: Thyroglossal cysts are the most common congenital anomalies of the neck and the treatment is surgical with satisfying outcome, low complication rates and small percentage of recidives.
Keywords: thyroglossal cyst; diagnostics; surgical procedure